HUBUNGAN ANTARA MOTIVASI BELAJAR DAN HASIL BELAJAR SISWA PADA MATERI STOIKIOMETRI KELAS XI SMA NEGERI 12 KENDARI - Nurul Anjani, Fadilah; Fahyuddin; Muh Alim Marhadi (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
This study aims to examine students’ level of learning motivation, describe their learning outcomes in stoichiometry, and analyze the relationship between the two. The research employed a quantitative approach with a correlational design. The participants consisted of 36 eleventh-grade students of SMA Negeri 12 Kendari in the 2025/2026 academic year, selected using simple random sampling. Data were collected through a learning motivation questionnaire and a learning outcomes test.The results indicated that students’ learning motivation was in the high category, with an average score of 76.04. Meanwhile, their learning outcomes were classified as good, with an average score of 78.96. The Spearman Rank correlation test showed a positive and significant relationship between learning motivation and learning outcomes, with a correlation coefficient of 0.350 and a significance value of 0.036 (p < 0.05).